Development and Performance Evaluation of a Re-circulatory Vegetable Moisturizer - Sunmonu, M. O.; Odewole, M. M.; Obajemihi, O. I.; Ayodeji, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2016)
A re-circulatory vegetable moisturizer for preventing wilting in vegetables was developed and its performance evaluation carried out. Freshly harvested Amaranthus vegetables were used for the experiments. The temperature and relative humidity were monitored daily. The vitamin A of this produce was determined at intervals of two days for 9 days. The effects of the storage parameters (temperature and relative humidity) on the nutritional value of the produce were determined using statistical analysis of variance (ANOVA). Further analysis by Duncan’s New Multiple Range Test (DNMRT) was carried out to compare the means. The vegetable moisturizer was evaluated by comparing the change in nutritional (vitamin A) of Amaranthus vegetable with hand wetting system and no wetting condition. The results showed that the moisturizer had higher mean vitamin A content (4.93mg/100g)compared to the mean vitamin A content of the manual wetting (4.88mg/100g) and no wetting condition (4.57mg/100g). The sensory characteristics showed that the Moisturizer was more desirable when compared to the manual wetting and no wetting condition after nine days. It was concluded that the Moisturizer preserved the nutritional and sensory characteristics (texture and colour) better than the manual and no wetting condition as a result of lower temperature, higher relative humidity and better water draining of the Moisturizer.